PENGARUH PEMBERIAN KOMPOS JERAMI PADI DAN MOL TERHADAP KETERSEDIAAN N, P, K, DAN PERTUMBUHAN JAGUNG DI TANAH ALLUVIAL - Gans Silalahi, Gio Andi; Yulies Vitri Indrawati, Urai Suci; Manurung, Rinto (Fakultas Pertanian, Universitas Janabadra, 2024)
Alluvial land in Indonesia, especially in West Kalimantan, has the potential as an agricultural area but has obstacles that can reduce productivity. Utilization of organic matter such as rice and mole straw compost is an alternative that can be used to overcome alluvial soil problems. This study aims to determine the effect of giving compost of rice straw and mole of banana tag on the availability of nutrients N, P, and K, and the growth of corn plants (Zea mays saccharata L.). The study was conducted on the land of Karya I Hamlet I Kuala Dua Village, Kubu Raya Regency. The study used the field experimental method with a complete random design pattern (RAL) with 1 factor, consisting of 5 treatment levels including J0 = 0 (control), J1 = 280 g/polybag (10 tons/ha), J2 = 560 g/ Polybag (20 tons/ha), J3 = 840 g/polybag (30 tons/ha), and J4 = 1120 g/polybag (40 tons/ha). Each treatment is repeated 5 times, and there are 25 polybags. The research parameters observed were soil pH, C-organic, N-total, P-available, K-Available, Plant Height, Stem Diameter, and Dry Root Weight. The results showed that the administration of rice straw compost and mole of banana tubes significantly affected soil pH, soil c-organic, soil phosphorus, plant height, stem diameter, and root dry weight. Keywords: corn, rice straw compost, and mol, alluvial land